A Smart Battery Management System with Charging and Discharging Analysis - Nikunj Jain; Krish Kathuria; Vanshdeep Saini; Inderpreet Singh; Gurmillian Singh Bains; Mehak; Dr. Rakesh Kumar Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The following research introduces a smart battery management system (BMS) which refines lithium-ion batteries in digital devices and grants for instantaneous remote monitoring. The framework utilizes IoT technology and an ESP8266 microprocessor in order to converge crucial battery metrics such as voltage, current, and temperature. A cloud-based analytics platform called ThingSpeak receives these data points, allowing for real-time display, data storage, and user notifications. The proposed smart BMS turns aside overburdening and superheating deter by improving battery performance via anticipatory alarms. A prototype version of the IoT-enabled battery monitoring system is examined with a TP4056 charging module and additional sensor components. This study highlights the importance of remote battery condition monitoring in maintaining the safety, lifespan, and efficiency of lithium-ion batteries in a variety of applications, such as compact consumer gadgets and utility- scaled energy storage. The study also illustrates high-tech surveillance methods and addressed the upcoming advancements in power sources to increase the battery health management even more. The smart BMS is remarkable itself from standard battery management approaches, that usually is deficient of proactive monitoring capabilities, by including real-time data analysis, cloud storage, and intelligent alarms. Future innovations such as AI-driven predictive modelling, multi-device compatibility, along with straight-forward system interfaces are addressed in the study’s conclusion. With these developments, IoT- based battery management systems are set as a revolutionary technology in digital device energy management, assisting effective and sustainable battery use in modern applications.